2020
DOI: 10.3389/fimmu.2020.570524
|View full text |Cite
|
Sign up to set email alerts
|

The Differential and Dynamic Progression of Hepatic Inflammation and Immune Responses During Liver Fibrosis Induced by Schistosoma japonicum or Carbon Tetrachloride in Mice

Abstract: However, in liver fibrosis caused by CCl 4 , Th1 cells occupied the dominant position, while proportions of Th2, Th17, and Treg cells decreased gradually. In conclusion, liver fibrosis was a complex pathological process that was regulated by a series of cytokines and immune cells. The pathological progressions and immune responses to S. japonicum or CCl 4 induced liver fibrosis were different, possibly because of their different injury mechanisms. The appropriate animal model should be selected according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Because there are various factors causing LF, and the pathogenesis and pathological process of different types of LF are different, the effects of macrophage polarization also vary. A study has shown that M1 macrophages and related pro-inflammatory cytokines are markedly increased in carbon tetrachloride (CCl 4 )-induced LF, whereas M2 macrophage polarization seems to predominate in schistosome infection-induced LF ( 194 ). Therefore, the inhibition of M1 and M2 macrophage polarization may respectively alleviate CCl 4 - and schistosome infection-induced LF.…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…Because there are various factors causing LF, and the pathogenesis and pathological process of different types of LF are different, the effects of macrophage polarization also vary. A study has shown that M1 macrophages and related pro-inflammatory cytokines are markedly increased in carbon tetrachloride (CCl 4 )-induced LF, whereas M2 macrophage polarization seems to predominate in schistosome infection-induced LF ( 194 ). Therefore, the inhibition of M1 and M2 macrophage polarization may respectively alleviate CCl 4 - and schistosome infection-induced LF.…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…Many types of immune cells are involved in the host immune response to S. japonicum infection, such as Th1, Th2, Th17 [ 15 17 ], Tfh [ 18 , 19 ], Treg cells [ 20 , 21 ], DCs [ 22 24 ] and γδ T cells [ 25 ]. Tfh cells are a fairly recently identified subset of CD4 + T cells that have a distinct gene expression profile and act independently of Th1, Th2 and Th17 cell lineages [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some literature has shown that the percentage of M1 macrophages in abdominal cavity after S. japonicum infection began to rise at 3 weeks after infection and began to decline at 8 weeks after infection. M2 macrophages were activated through m1-to-m2 phenotype transformation and began to rise from 8 weeks, but with different tissues, there may be differences in activated macrophages, which mainly depends on the changes of cytokines ( Zhu et al., 2014 ; Song et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%